Implementasi Metode Additive Ratio Assessment (ARAS) Dalam Penilaian Kinerja Perangkat Desa Pada Kantor Pemerintahan Desa Tebing Linggahara - Siti Sundari (Journal of Computing and Informatics Research, 2024)
Village Apparatus is a public service personnel who has duties and responsibilities towards community service, assisting the village head in carrying out his duties. So far, the performance assessment of village apparatus at the Tebing Linggahara Village government office is still manual so it takes a long time. Therefore, a decision support system is needed that can provide convenience in assisting the local government to assess the performance of village apparatus at the Tebing Linggahara Village government office. In this study, a decision support system is proposed that can assist in assessing the performance of village apparatus, namely using the Additive Ratio Assessment (ARAS) method. The ARAS method is part of the Multi Criteria Decision Making (MCDM) which is closely related to the Decision Support System. The ARAS method can also be used to make decisions from each alternative, then from each alternative has several criteria that are used as a reference in calculations using the ARAS Method. The ARAS method is used for ranking values. With this ranking method, Aminah Ritonga (A3) is the village apparatus with the best performance in the Tebing Linggahara Village Government office with the largest value of 6.5187, followed by Ramlan Saragih (A12) in second place with a value of 3.0966, then Samsuddin (A2) in third place with a value of 2.8224. It is hoped that the assessment of village apparatus performance will be more precise because it is based on the predetermined criteria and weight values, so that it will get maximum results.